Two concepts for making sense of social media presence: Inbound marketing and content marketing - Arroyo-Vázquez, Natalia (Anuario ThinkEPI, 2017)
Inbound marketing and content marketing are used by social media as a way to achieve the goals of a brand and to attract customers. In this text, practical applications of both concepts for libraries are analyzed. In addition, examples are given and main implications are revealed.